Neuromodulation: Actions of Dopamine, Retinoic Acid, Nitric Oxide, and Other Substances on Retinal Horizontal Cells - McMahon DG; Dowling JE (Eye and Brain, 2023)
Douglas G McMahon,1 John E Dowling2 1Department of Biological Sciences, Vanderbilt University, Nashville, TN, 37235, USA; 2Department of Molecular and Cellular Biology, Harvard University, Cambridge, MA, 02138, USACorrespondence: Douglas G McMahon, Department of Biological Sciences, Vanderbilt University, Nashville, TN, 37235, USA, Email douglas.g.mcmahon@vanderbilt.eduAbstract: Whereas excitation and inhibition of neurons are well understood, it is clear that neuromodulatory influences on neurons and their synapses play a major role in shaping neural activity in the brain. Memory and learning, emotional and other complex behaviors, as well as cognitive disorders have all been related to neuromodulatory mechanisms. A number of neuroactive substances including monoamines such as dopamine and neuropeptides have been shown to act as neuromodulators, but other substances thought to play very different roles in the body and brain act as neuromodulators, such as retinoic acid. We still understand little about how neuromodulatory substances exert their effects, and the present review focuses on how two such substances, dopamine and retinoic acid, exert their effects. The emphasis is on the underlying neuromodulatory mechanisms down to the molecular level that allow the second order bipolar cells and the output neurons of the retina, the ganglion cells, to respond to different environmental (ie lighting) conditions. The modulation described affects a simple circuit in the outer retina, involves several neuroactive substances and is surprisingly complex and not fully understood.Keywords: neural network adaptation, vision, synaptic modulation, gap junctions, glutamate receptors, GABA receptors